Relationship between Parents Education Level and Mother's Knowledge with Nutritional Status of Children Aged 6 - 24 Months at Tareran Community Health Center Working Area at Tareran Sub-District, South Minahasa Regency - Bernardus, Harry H.; Mamuaja, Christine F.; Oessoe, Joachim Y. E. (Pascasarjana Unsrat, 2015)
Consequency of low birth weight (LBW) have a greater risk of death than babies of normal weight. Some findings indicate that in developing countries and developed countries there is a link between low birth weight infants with chronic diseases in adulthood. Based on the results of Nutritional Status Monitoring (NSM) conducted South Minahasa District Health Office 2013 suggests that the nutritional problems of children under five in South Minahasa district needs serious attention, which is still the presence of malnutrition-less. This research has a goal to analyze the relationship between education level of parents and maternal knowledge with nutritional status of children aged 6 - 24 months in Tareran Sub-district of South Minahasa Regency. Research is done in April - Mei 2015 uses descriptive analytic method with cross sectional approach. Results of the chi-square test showed that both the education level of the father and mother's education level has no relation with the nutritional status of children, in which the test results are known that the value of p = 0.434 for the father's education level and the value of p = 0.608 for the mother's education level, and both has a value greater than the value of Î± (0.05). Knowledge mother has a relationship with the nutritional status of children, where the value of p = 0.037 or p<0.05. Knowledge affect a person's behavior, because the understanding of the object is known, in the context of this study mother's knowledge about health and nutrition has given understanding to act. Chi-square test results showed that mothers whose knowledge is good (70,59 %) have children with good nutritional status, and vice versa. Keywords : children aged 6 - 24 months, mother's knowledge, nutritional status, parents education level